Pengembangan e-LKPD Terintegrasi Kearifan Lokal Bengkulu Utara Berbasis Aplikasi Android untuk Meningkatkan Hasil Belajar - Aprianti, Lilien (UNIB Press, 2024)
Teacher-centered learning causes students to experience boredom quickly and is unable to construct their own knowledge which results in a decrease in student learning outcomes. This study aims to test the feasibility and effectiveness of student electronic work sheet integrates Bengkulu Utara local wisdom in non-fiction text topic to improve student study result. This research is research and development (R & D) with three main steps, namely: preliminary study, product design and product testing. Bengkulu Utara local wisdom-based student electronic work sheet product developed was tested for its effectiveness in fifth grade students at SDN 046 Bengkulu Utara using a quasi-experiment non-equivalent pretest-posttest control group design. Data collection used learning evaluation tests. The data analysis technique used the independent sample t test. The results of the study show that Bengkulu Utara local wisdom-based student electronic work sheet is feasible to use in learning activities and is effective in improving student study result.